K-Means Clustering for the Relationship Between Mathematical Problem Solving Ability and Mathematical Communication Ability - Dermawan, Rendi; Hidayat, Dayat (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2025)
The purpose of this research is to examine the relation between mathematical problem-solving ability and mathematical communication ability by applying k-means clustering in grouping students. This research uses a quantitative approach with a correlational research method. The population of this research is the eighth-grade students of SMP Negeri 3 Purwakarta, with a total of 355 students. The sampling technique uses simple random sampling and is calculated using the Slovin formula, so the total sample is 79 students. The instrument used in this research is a subjective test in the form of questions of mathematical problem-solving ability and mathematical communication ability. The data analysis technique in this research is k-means clustering to group the data and correlation hypothesis test. The results show that 37 students fall into Cluster 1 (high-ability), 28 students into Cluster 2 (medium-ability), and 14 students into Cluster 3 (low-ability). In all samples and cluster 1, it is stated that at the 95% confidence level there is a significant relationship between mathematical problem-solving ability and mathematical communication ability. However, in all samples, it shows a weak relationship and the contribution of mathematical problem-solving ability to mathematical communication ability is 9.22%, and vice versa. While in Cluster 1, it shows a medium relationship and the contribution of mathematical problem-solving ability to mathematical communication ability is 31.2%, and vice versa. In Cluster 2 and Cluster 3, the analysis indicates that although there is a relationship at the 95% confidence level, it is not statistically significant.